Evaluation of patient satisfaction with nursing services before and after implementation of the Health System Transformation Plan in Iran: A cross‐sectional study - Yadollah Jannati; Abolfazl Babajani; Maedeh Ghasemi Kolaei; Hossein Mohsenipouya; Nouraddin Mousavinasab; Mohammad A. H. Gorji; Mohammed A. Mamun (Health Science Reports, 2022)
Abstract Background and Aims How healthcare service delivery is achieved after implementing the Health System Transformation Plan (HSTP) is investigated in the present study by assessing the patients' satisfaction with nursing care services compared to before HSTP. Methods This cross‐sectional study was conducted in Iranian hospitals during two periods, that is, before (N = 300) and after (N = 279) HSTP, whereas the Patient Satisfaction Instrument was used to assess the satisfaction with nursing services. Results About 57.7% and 4.7% of the patients were dissatisfied with nursing care services, whereas 34% and 77.4% for moderate satisfaction, and 8.3% and 17.9% for total satisfaction, before and after HSTP, respectively. The mean score of overall satisfaction was 57.33 (±11.17) and 70.84 (±11.99) before and after HSTP, respectively (p < 0.001), which represents there is an improvement in healthcare services delivery after HSTP. Although none of the sociodemographic factors were significantly associated with satisfaction, higher satisfaction was found among the coronary care unit (CCU) hospitalized patients. Conclusion The patients' overall satisfaction with nursing care services after HSTP was increased, although higher satisfaction was observed in the patients of special wards such as CCU. Therefore, using more care facilities and equipment and engaging more skilled nursing staff in other wards is highly recommended.